Кельти за межами «кельтського світу»: моделі етнокультурної взаємодії на периферії латенської культури - Казакевич, Г.М. (Археологія, 2007)
Нові археологічні відкриття, дослідження в галузі лінгвістики та археогенетики дають змогу по-новому подивитися на процеси латенізації археологічних культур і кельтизації етнічних спільнот раннього залізного віку. Данные археологии, лингвистики и археогенетики, введенные в научный оборот в течение последних десятилетий,
вынуждают пересмотреть некоторые устоявшиеся взгляды на древних кельтов и этнокультурные процессы раннего
железного века, в которые они были вовлечены. Гипотеза о значительном однообразии латенской археологической
культуры от Атлантики до Дуная не подтвердилась и сегодня уступает место подходу «кельтоскептиков», согласно
которому под древними кельтами следует понимать конгломерат племен, объединенных использованием кельтских
диалектов и некоторых общих черт материальной и духовной культуры. Новые источники позволяют реконструировать несколько моделей кельтизации, в частности сравнительно однородные кельтские этнические общности,
сформировавшиеся независимо от становления латенской культуры (кельтиберы, носители культуры Голасекка), а
также достаточно однородные в этническом отношении группы кельтов, утративших латенские традиции вследствие переселения на новые земли (малоазийские галаты), и генетически не связанные с центральноевропейскими
кельтами, но при этом пользующиеся кельтскими диалектами носители латенской культуры (Британские острова).
Эти модели могут быть использованы для более глубокого понимания процессов латенизации археологических
культур Восточной Европы. Recent discoveries in fields of archaeology, linguistics and archaeogenetics brought to revision some traditional opinions
about the ancient Celts and ethnical and cultural processes of Early Iron Age in which they were involved. The hypothesis
about homogeneous and unified La Téne culture from Atlantic to the Danube had been recently rejected and gave way
to the “celtosceptical” approach, according to which the Celts are considered as a conglomeration of tribes united by the
common use of Celtic dialects and some common features of social structure, religion and material culture. New sources
allow the author to reconstruct different patterns of celticization, in particular, relatively homogenous Celtic communities
which were formed independently from La Téne culture (Celtiberians of Golasecca culture); also sufficiently homogenous
in ethnical perspective communities of the Celts which lost their La Téne traditions due to migrations on new territories
(Galatians of Asia Minor); as well as communities genetically not related to the Central European Celts which, however,
used Celtic dialects and La Téne traditions (British Islands). Those patterns could be used in fundamental understanding
of latenization processes of the archaeological cultures of Eastern Europe.